The Lived Fracture Experience (LiFE) study: A mixed methods qualitative study research protocol exploring the lived experiences of fracture non-union patients - Irene Yang; Carol Porteous; Hamish Simpson (PLoS ONE, 2025)
Background Fractures are a common and a major cause of disability and death, with up to 10% of fractures failing to heal normally. These fractures are called “fracture non-unions”. Currently, debate on the impact of non-union in the medical and research communities exists. Unfortunately, this indirectly minimizes the impact of fracture non-unions, and hinders further research work which could reduce unnecessary patient suffering. In this study, we aim to explore the lived experiences of fracture non-union patients in one-on-one interviews to determine whether fracture non-union is a burden for patients, and if so, to outline the burden on patients and their close circles. Methods Eligible participants will include adult patients who currently have/previously (in the last 36 months) had a long bone fracture that has not healed normally. Data will be collected through in-depth face-to-face or telephone interviews, complemented by quantitative data captured using the standardized Euroqol EQ-5D-5L questionnaire. With consent, interviews will be audio-recorded and transcribed verbatim. Using NVIVO software, we will develop grouped codes and categories to describe and provide insight into the experience of fracture non-union patients. EQ-5D-5L, and EQ VAS data will be presented using a measure of central tendency and a measure of dispersion to provide insight into the overall health related quality of life for patients. Ethics and dissemination The study was approved by the Health Research Authority and Health and Care Research Wales Approval (approval date: 27 March 2024; IRAS project ID: 337652). Results from this study aim to improve the information and support provided to fracture non-union patients. Findings will be disseminated to the study participants, healthcare professionals, and local commissioners through peer-reviewed articles and at academic conferences.